Waste-to-Energy: Tapioca Solid Waste-to-Ethanol - Karunakaran, K.; Manjunathan, S.; Samson Nesaraj, A. (Asian Journal of Chemistry, 2016)
Considerable attention has been given in recent years to the development of alcohol production technology due to increasing demand for petrol. Ethanol has been known for a long time, being perhaps the oldest product obtained through traditional biotechnology. Several renewable carbohydrate resources have been tested for the production ethanol as a liquid fuel. It is expected that the demand for ethanol for transportation purposes will increase drastically in the near future. The usage of bio-based products and bio-energy will reduce the import of oil products. Sugarcane is the main raw material for ethanol production in India. Similar to ethanol production from sugarcane, the utilization of bio-waste as an alternate raw material can quench the demand for ethanol. By using biomass-derived ethanol, a net reduction in the levels of carbon dioxide (the main greenhouse gas) could range from 60-90% relative to gasoline consuming vehicles. This paper aims to quantify the availability of raw material and develop suitable metabolic engineering for the bio-ethanol production using microbial platforms from tapioca solid waste.